Generational dynamics in the labor market: Global trends and local realities in Romania - Mihaela-Georgiana Oprea; Mihaela-Irma Vlădescu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The world is constantly changing, which leads to changes in the labor market. Both globally and in Romania, the labor market is currently in an extremely difficult phase, but at the same time it offers many opportunities for reshaping, reinventing and optimizing. Globalization, automation, development, population growth, aging and organizational structures all contribute to an unpredictable labor market. Technological development and training adapted to digitalization have influenced the characteristics of each generation entering the labor market. Although there is consensus on the name and general time period of each designated generation, there is no agreement on the exact years each generation begins and ends. To understand how and why generational conflict occurs, it is important to know what characteristics distinguish each generation. Because of the specific characteristics of each generation, conflict can occur in the workplace. Challenges that have arisen in the labor market in recent years, such as the need for flexible and/or remote work have imposed adaptation to new technologies. This has led to an increase in demand for personnel familiar with the use of digital skills. Although there is a general trend toward digitization and adaptation to new technologies, Generations Y and especially Z use the Internet to a greater extent than the other generations, making them the most important source of workers in the IT sector.
Keywords: J80; F82; J70; 330; generations; labor force; inequalities; ages; labor market; digitization